The next person you meet in heaven ebook The sequel to the five people you meet in heaven. - Albom, Mitch (2018)
In this enchanting sequel to the #1 bestseller The Five People You Meet in Heaven, Mitch Albom tells the story of Eddie's heavenly reunion with Annie—the little girl he saved on earth—in an unforgettable novel of how our lives and losses intersect. In Mitch Albom's beloved novel, The Five People You Meet in Heaven, the world fell in love with Eddie, a grizzled war veteran-turned-amusement park mechanic who died saving the life of a young girl named Annie. Eddie's journey to heaven taught him that every life matters. Now, in this magical sequel, Albom reveals Annie's story. The accident that killed Eddie left an indelible mark on Annie. It took her left hand, which needed to be surgically reattached. Injured, scarred, and unable to remember why, Annie's life is forever changed by a guilt-ravaged mother who whisks her away from the world she knew. Bullied by her peers and haunted by something she cannot recall, Annie struggles to find acceptance as she grows. When, as a young woman, she reconnects with Paulo, her childhood love, she believes she has finally found happiness. As the novel opens, Annie is marrying Paulo. But when her wedding night day ends in an unimaginable accident, Annie finds herself on her own heavenly journey—and an inevitable reunion with Eddie, one of the five people who will show her how her life mattered in ways she could not have fathomed. Poignant and beautiful, filled with unexpected twists, The Next Person You Meet in Heaven reminds us that not only does every life matter, but that every ending is also a beginning—we only need to open our eyes to see it.